2018
DOI: 10.1017/qua.2018.141
|View full text |Cite
|
Sign up to set email alerts
|

The environmental impact of a pre-Columbian city based on geochemical insights from lake sediment cores recovered near Cahokia

Abstract: Cahokia is the largest documented urban settlement in the pre-Columbian United States. Archaeological evidence suggests that the city, located near what is now East St. Louis, Illinois, began to rapidly expand starting around AD 1050. At its height, Cahokia extended across 1000 ha and included large plazas, timber palisade walls, and hundreds of monumental earthen mounds. Following several centuries of occupation, the city experienced a period of gradual abandonment from about AD 1200 to 1400. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Greater Cahokia's regional population was at its lowest in the fifteenth century, marking the end of a nearly continuous demographic decline that began 300 years earlier (Emerson 2018; Milner 2006; Pauketat and Lopinot 1997; White et al 2018). Numerous explanations for the decline have been put forward (Benson et al 2009; Bird et al 2017; Emerson and Hedman 2015; Kelly 2009; Lopinot and Woods 1993; Munoz et al 2015; Pauketat 2018; Pauketat et al 2013; Pompeani et al 2019; White et al 2019), but its reversal has not been discussed. In eastern North America, protohistoric sites are identified on the basis of native-made materials in association with European trade goods in locations that do not appear on maps and that are not mentioned in historic records or European travel accounts (Ehrhardt 2010; Mazrim and Esarey 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Greater Cahokia's regional population was at its lowest in the fifteenth century, marking the end of a nearly continuous demographic decline that began 300 years earlier (Emerson 2018; Milner 2006; Pauketat and Lopinot 1997; White et al 2018). Numerous explanations for the decline have been put forward (Benson et al 2009; Bird et al 2017; Emerson and Hedman 2015; Kelly 2009; Lopinot and Woods 1993; Munoz et al 2015; Pauketat 2018; Pauketat et al 2013; Pompeani et al 2019; White et al 2019), but its reversal has not been discussed. In eastern North America, protohistoric sites are identified on the basis of native-made materials in association with European trade goods in locations that do not appear on maps and that are not mentioned in historic records or European travel accounts (Ehrhardt 2010; Mazrim and Esarey 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, the spatial distribution of pre-Columbian Pb pollution within the Black Bottom, and indeed at other archaeological sites across the midcontinental United States, is not known at this time. It is probable that other sites where galena trade, processing, and utilization occurred also contain legacy pre-Columbian Pb pollution, as suggested by increased Pb in Horseshoe Lake near Cahokia (near present-day East St. Louis, Illinois) during the Mississippian occupation (Pompeani et al, 2019). Detailing spatiotemporal and source variability in Pb pollution provides important information about how pre-Columbian Native Americans interacted with and utilized their landscape and its resources.…”
Section: Discussionmentioning
confidence: 99%
“…Archaeological records indicate that galena (PbS, a lead-sulfide mineral and primary lead ore) was utilized by pre-Columbian Native American populations in eastern North America for nearly 10,000 yr (Walthall, 1981). While some evidence has indicated that pre-Columbian societies generated limited lead (Pb) pollution as a biproduct of copper mining (Pompeani et al, 2013) and biomass burning (Bird et al, 2019;Pompeani et al, 2019), there has been no conclusive evidence that the extraction, trade, and use of galena specifically resulted in environmental impacts. This contrasts with other regions with long histories of Pb ore utilization, like Europe and South America, where early Pb pollution signals are widely distributed and well preserved in natural archives (e.g., Bränvall et al, 2001;Cooke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In North America, there is little evidence of pre-European use of base metals 50 , so low levels of anthropogenic Pb pollution prior to this point is to be expected. A small increase during the Mississippian period (1150-1450 CE) in the North American synthesis may be observed, reflective of limited pre-Colombian pollution on the continent 51,52 , represented by a low-probability changepoint from 1100 CE onwards (Fig. 2C).…”
Section: Assessing Regional Variability and Representativeness Of Pb mentioning
confidence: 98%